The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/10242420290004910
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-catalyzed Preparation of Novel Fatty Acid Derivatives of Pyridoxine with Surfactant Activity

Abstract: A series of novel fatty acid derivatives of pyridoxine, one of the three members of the vitamin B 6 group, has been prepared. These products were obtained using an enzymatic approach. Several lipases catalyzed esterification and transesterification reactions of pyridoxine with carboxylic acid or alkyl carboxylates showed a remarkable regioselective behavior; only monoacyl derivatives were obtained. The surfactant activity, composition and clean enzymatic methodology applied in the preparation of these products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Estradiol esterification with oleic acid was compared to transesterification using ethyl oleate as acyl donor. We observed that esterification with oleic acid was much better with more than 75 % formation of 3h while the use of ethyl ester gave very poor yield not exceeding 39% after 96 h. Interestingly, the same results were also reported by us in enzymatic acylation of pyridoxine 28 and dehydroepiandrosterone 23 and other authors in the preparation of cholesterol-29 and phytosterols oleate. , 30 Therefore, in all further experiments with CRL, esterification processes were chosen using free fatty acids as acyl donors.…”
Section: B Effect Of Nature Of the Acyl Donorsupporting
confidence: 75%
“…Estradiol esterification with oleic acid was compared to transesterification using ethyl oleate as acyl donor. We observed that esterification with oleic acid was much better with more than 75 % formation of 3h while the use of ethyl ester gave very poor yield not exceeding 39% after 96 h. Interestingly, the same results were also reported by us in enzymatic acylation of pyridoxine 28 and dehydroepiandrosterone 23 and other authors in the preparation of cholesterol-29 and phytosterols oleate. , 30 Therefore, in all further experiments with CRL, esterification processes were chosen using free fatty acids as acyl donors.…”
Section: B Effect Of Nature Of the Acyl Donorsupporting
confidence: 75%
“…[21][22][23] We have also performed enzyme-catalysed deacylation reactions on various steroids such as cholestanes, androstanes and pregnanes, which demonstrated the ability of enzymes to discriminate between acetoxy substituents in these substrates, furnishing deacetylation reactions at different positions in the steroid skeleton. While Candida rugosa lipase removed acetyl groups situated in ring A, Candida antarctica lipase was preferentially active on substituents located in ring D. [24,25] With the aims of extending the biocatalytic approach to other natural products and of preparing a family of derivatives difficult to obtain through traditional chemical methods, in order to study the structure/activity relationship, we decided to apply an enzymatic approach to diterpenoids such as ent-kauranes.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have applied this methodology in the esterification of carboxylic acids of variable chain length including fatty acids with ethanol 12,14 and some natural alcoholism such as steroids and vitamin B 6 . 15,16 Herein, compounds 2a-f were obtained through esterification of the 2-oxoglutaric acid 1 catalyzed by lipases from several sources: from yeast: Candida rugosa lipase (CRL), Candida antarctica lipase (CAL); Lipozyme from the fungus Mucor miehei (LIP), and lipase PS (PSL) and PS-C (PSL-C) from Pseudomonas sp. The five commercial lipases were tested in the esterification of 1 with ethanol to obtain 2b.The lipase from Candida antarctica (CAL) gave the most satisfactory results at both temperatures.…”
Section: Resultsmentioning
confidence: 99%